Gestión de riesgos en seguridad industrial en el área de Máquinas y Herramientas en el laboratorio de la carrera de Ingeniería Industrial - Damian Moyota, Adriana Vanessa (2025)
This research project was carried out in the Machines and Tools area of the Industrial Engineering laboratory to manage the mechanical and physical risks identified in the different existing workstations. The identification of mechanical and physical risks was carried out using an observation guide and a checklist that was applied to the different processes of the machines found in each workstation in the laboratory. Using the NTP 330 methodology, the criticality of the risks could be established to obtain the risk level and suggest prevention measures. Based on the results obtained in evaluating mechanical and physical risks and the NTE INEN—ISO 3864-1:2013 standard, safety signage was implemented as a preventive measure to safeguard the well-being and health of the people who occupy the Machines and Tools laboratory. Risk management in industrial safety is essential to preventing accidents and ensuring a safe work environment in machine processes. It involves the identification and evaluation of risks, as well as the implementation of preventive and corrective measures that minimize dangers through a safety culture.